Organic Residues in Control of Fusarium oxysporum f. sp. passiflorae in Yellow Passion Fruit (Passiflora edulis f. flavicarpa) (2015)
The fusarium is an important disease in yellow passion fruit that causes severe limitation in fruit production and reduced longevity of the orchards. This study aimed to evaluate the effect of organic residues in vitro and in vivo as alternative control in Fusarium of yellow passion fruit, caused by Fusarium oxysporum f. sp. passiflorae. Six concentrations were evaluated in vitro (0, 2, 4, 6, 8 and 10 %), in the form aqueous extracts, in the mycelial growth inhibition and in vivo (0, 20, 40, 60, 80 and 100 g kg-1), incorporated on soil for the Fusarium control. The organic residues used were eucalyptus leaves, bagasse babassu and cassava peeling. These residues were subjected to nutritional and microbiological analyzes. The pathogenicity of isolates tested was confirmed, which proves the presence of Fusarium in yellow passion fruit in vivo. Bagasse babassu presented the highest N, P and K concentration. Fungal species with higher frequency were Penicillium sp., Aspergillus niger, Aspergillus flavus and Aspergillus ochraceus. I There was a significative inhibition in vitro of the bagasse babassu extract at 6 % and other two residues at 10 %. In vivo the 60 g kg-1 of bagasse babassu and 80 g kg-1 of cassava peeling were efficient for Fusarium control. Eucalyptus leaves presented no effect on development of Fusarium wilt in yellow passion fruit in the greenhouse. The organic residues can be used for the Fusarium control in yellow passion fruit.